The sugar camp quilt eaudiobook - Chiaverini, Jennifer (Elm Creek Quilts, 2015)
History is thick with secrets in The Sugar Camp Quilt, seventh in the beloved Elm Creek Quilts series from bestselling author Jennifer Chiaverini. Set in Creek's Crossing, Pennsylvania, in the years leading up to the Civil War, the novel follows Dorothea Granger's passage from innocence to wisdom against the harrowing backdrop of the American struggle over slavery. She discovers that a quilt she has stitched for her uncle Jacob with five unusual patterns of his own design contains hidden clues to guide runaway slaves along the Underground Railroad. The heroic journey she undertakes leads to revelations about her own courage and resourcefulness — newfound qualities that may win her the heart of the best man she has ever known.